Criminal Liability of Juvenile Drug Dealers in the Perspective of Islamic Takzir Law - Kusnadi, Arman; Najmudin, Deden; Azazy, Yusuf (Al-Qanun: Jurnal Kajian Sosial dan Hukum Islam, 2025)
This study examines the criminal liability of juvenile drug dealers in Court Decision Number 2/Pid.Sus-Anak/2022/PN Crp, using a normative legal approach and field case analysis. The case involves two 17-year-old minors who were found guilty of selling drugs under the instruction of an adult. The judge sentenced them to 3 years and 6 months in prison along with 3 months of vocational training. This paper highlights the alignment between Law No. 11 of 2012 on the Juvenile Criminal Justice System and the perspective of Islamic criminal law. In Islamic law, such acts are considered jarimah (criminal offenses) and are legally analogized to khamr (intoxicants). The takzir approach allows judges to impose educational and preventive sanctions. The main contribution of this study is its comparative analysis between normative legal provisions and judicial practice, while exploring the relevance of the takzir concept in ensuring child protection and proportional justice.